Efficiency of consumer behaviour and digital ecosystem in the generation of the plastic waste toward the circular economy - Khatami, Fahimeh; Vilamová, Šárka; Cagno, Enrico; De Bernardi, Paola; Neri, Alessandra; Cantino, Valter (Journal of environmental management, 2023)
A circular economy can help reduce the impact of plastic waste using reaction, resilient, and digital approaches. In addition, it can facilitate reducing plastic consumption. In this regard, consumer behaviour and digitalization are deemed to be two main factors that play major roles in the implementation of a circular economy of plastic waste. The idea of this paper is to understand the relevance of consumer behaviour and digital ecosystem efficiency on plastic waste at the country level. Hence, the efficiency of eight European countries in the generation of plastic waste was analysed using international databases and the statistical method of receiver operation characteristic (ROC). For this purpose, the dependent actual state variables were defined as plastic waste generations, and the independent test variables were defined as digital ecosystem and consumer behaviour factors. ROC plots for the determination of the area under the curve (AUC) indices were produced between the mentioned state and test variables. The results revealed that consumer behaviour increases the higher generation of plastic waste (AUC >0.6), indicating that consumer behaviours have high effectiveness on the generation of plastic waste in European countries. Furthermore, the results indicated that the digital ecosystem has a controlling role in the generation of plastic waste in the study area (AUC <0.5), indicating the digital ecosystem factors associated with the low generation of plastic waste. The overall consumer behaviour in the selected European countries showed an unskilled role regarding the higher generation of plastic waste, while the digital ecosystem context showed a mitigating role in decreasing plastic pollution. The confirmation of the research hypotheses leads to some managerial propositions for the circular economy of plastic waste in the area of consumer behaviour and digitalization. The results propose an elaborated framework, including a reduction in waste generation, recycling in waste circulation, recovery in waste valorization, and efficiency in resource consumption by the digitalization of design technology and education in consumer behaviour for the circular management of plastic waste.
Keywords: Digital ecosystem; Plastic waste; chování spotřebitelů; Consumer Behavior; Recycling; Consumer behaviour; European countries; Receiver operation characteristic (ROC); plastické hmoty; ekosystém; nakládání s odpady; recyklace; Ecosystem; Waste Management; Circular economy; Plastics